Functional gastrointestinal disorders in patients with intellectual disability. Issue 2 (14th May 2021) - Javaid, Amir; Rushforth, Emma; Sajja, Srikanth; Michael, Dasari
Abstract : Gastrointestinal symptoms are common in the presentation of some psychiatric disorders such as somatisation disorder, anxiety disorders, eating disorders and substance abuse. Gastrointestinal (GI) disorders can also present with psychological symptoms. Furthermore, medications prescribed for GI disorders can cause psychiatric side‐effects. To better understand this complex relationship in the context of intellectual disability, we present 10 adult patients who had accompanying functional gastrointestinal disorders with adverse impact on their mental health.